Pengaruh Penambahan Serat Kapas (Gossypium sp.) Terhadap Kekuatan Tekan Resin Komposit Flowable - Inaray, Pradhica Shanaz, Drg. Dendy Murdiyanto, MDSc (2017)
Flowable composite resin is one of the restorative materials that has a weakness on compressive strength. One of ways to add the compressive strength is by the addition of fiber. Cotton fiber is a natural fiber which has a good mechanical properties. The purpose of this research was to know the influence of adding cotton fiber to compressive strength on flowable composite resin and to know the increase of compressive strength of flowable composite resin with the addition of cotton fiber (Gossypium sp.). This research was using post test-only design design. The object of this study was a flowable composite resin sample with the total of 32 samples divided into two groups: control group and treatment group.The result The result of this research was showed by independent t-test showing significant value (<0,05) between control group with mean of 249,614 Mpa and treatment group with mean of 266,177 Mpa. the conclution of the research was addition of cotton fiber had influence the compressive strength of flowable composite resin. The addition of cotton fiber influence the increase of compressive strength on flowable composite resin with the addition of cotton fibers